2016
DOI: 10.1371/journal.pone.0168928
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Drought Events in the Geochemical Records of the Lacustrine Deposits in the Southeastern Tibetan Plateau

Abstract: Lacustrine deposits at the margin of the southeastern Tibetan Plateau (SETP) are sensitive indicators for the evolution of the southwest Asian monsoon (SWAM) during the Quaternary. Thus, they can provide insight into the Quaternary climatic history and their relationship with global climatic changes. The results of the geochemical analysis of the Xiaozhongdian Basin section at the SETP suggest that SiO2 had the highest content of the major elements followed by Al2O3. The order of the abundance of the major ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Consistent with previous studies showing that insulin has pro-proliferative effects on various cell types [ 12 , 14 , 22 ], we demonstrated that insulin at concentrations higher than 2.5 μ M dose-dependently increased the number of UCM-MSC in SFM via promoting their proliferation ( Figure 1(a) ). However, it should be noted that, despite obtaining similar results in UCM-MSC, several investigators reported that insulin at merely nanomolar concentrations significantly increases the proliferation rate of human astrocytes and hepatocytes within 72 h [ 23 , 24 ], which is inconsistent with our data showing that physiologically relevant concentrations of insulin (0.1–1.0 μ M) had no significant effect on UCM-MSC proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies showing that insulin has pro-proliferative effects on various cell types [ 12 , 14 , 22 ], we demonstrated that insulin at concentrations higher than 2.5 μ M dose-dependently increased the number of UCM-MSC in SFM via promoting their proliferation ( Figure 1(a) ). However, it should be noted that, despite obtaining similar results in UCM-MSC, several investigators reported that insulin at merely nanomolar concentrations significantly increases the proliferation rate of human astrocytes and hepatocytes within 72 h [ 23 , 24 ], which is inconsistent with our data showing that physiologically relevant concentrations of insulin (0.1–1.0 μ M) had no significant effect on UCM-MSC proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…The stained sections were evaluated for EBIV immunoreactivity by Image-Pro Plus 6.0 software (Media Cybernetics, Inc., Silver Spring, MD, United States), and the accumulated optical density (IOD) and the corresponding brown-yellow positive area were provided with three randomly selected fields of view (200×). Finally, each group was represented by the accumulated optical density IOD (SUM; Zhang et al, 2016 ; Liu et al, 2019 ). All the above were performed at Wuhan Biotechnology Corporation.…”
Section: Methodsmentioning
confidence: 99%
“…Yunnan covers a total area of 394,000 km 2 , and it has the type of complex and diverse landscape, and the mountainous area accounts for more than 87%. On account of influences of Indian monsoon, East Asian monsoon, westerly wind and the Tibet Plateau, it has abundant precipitation with an average annual rainfall of 1280 mm, unbalanced distribution of precipitation in season and region, the rainy season (May to October) accounts for over 80% (Zhang et al, 2016). The vegetation is mainly composed of a subtropical evergreen broadleaved forest, a subalpine coniferous forest, a tropical rainforest and a tropical seasonal rainforest (Niu et al, 2020).…”
Section: Study Areamentioning
confidence: 99%